Author Reply: The "Social" Is Not Merely Another Level of Reality. (October 2014) - Mesquita, Batja
It is time to abandon essentialism in emotional research: Our sociodynamic model (Mesquita & Boiger, 2014) proposes to study emotions as contextualized processes, rather than as states. This does not mean eschewing mental processes, but rather studying them dynamically and in open interaction with their environment. Our proposal is not to shift the focus of emotion studies to a different level. Rather, placing emotions in their social context renders their psychological qualities understandable and predictable. This is illustrated by some examples from my own cross-cultural research.